PERANCANGAN PENGELOLAAN JARINGAN IT PADA INSTITUT SAINS & TEKNOLOGI AKPRIND MENGGUNAKAN TEKNOLOGI VPN (VIRTUAL PRIVATE NETWORK) - Masero, Agnesie Pratiwi; Triyono, Joko; Andayati, Dina (Jurnal Jarkom, 2013)
ABSTRACTWhile this time, in particularly in Institut Sains & Teknologi AKPRIND Yogyakarta, process of data exchange is dtill manually. The lecture is still has problem in data sending, where as mostly has used computer nor internet, but has not integrated well. However recent problem is, communication way in diffrent area, such as in remote distance. The communication way in remote distance able to be complement or by internet and email for data sending. Therefore it need private network for an easy file acces forward a different location, in order that it is easier in data exchanging process though in distance. The benefit of this research are to anable the cooperation between remote distance people by computere network, both in data exchanging nor communication establish and also enable to acces or obtain information in remote distance. In planning of Information Technology Networking Management of Institut Sains & Technology AKPRIND by using VPN-PPTP technology. In this VPN-PPTP palnning, using Public Static IP which is palced in 6 Jarinet Laboratory of Institut Sains & Technology AKRPIND. VPN-PPTP network use public IP of computer Laboratory 6 Jarinet with IP 202.91.10.217. However in topology VPN-PPTP is passed by gateway campus III of Institut Sains & Technology AKPRIND Yogyakarta network in order that could be connected to internet.Planning of IT networking management of Institut Sains & Technology AKPRIND use VPN technology is able being an acces facility of local network and usage of resources of local network which is not depent on condition of acces location, and transferring process velocity and pass time of upload or downloading in VPN network as still very affected by measure and type of sanding file.Â Keywords : network, VPN-PPTP, IP, Internet, networking plan